Exploring the impact of workload, organizational support, and work engagement on teachers’ psychological wellbeing: a structural equation modeling approach - Wang, Yonggang (Frontiers in Psychology, 2024)
Introduction This study delves into the intricate relationships among workload, perceived organizational support, work engagement, and psychological wellbeing within the context of 572 secondary school teachers in China. Methods Utilizing structural equation modeling (SEM), this research rigorously examined construct validity and the intricate interrelationships among latent variables. The data were collected and analyzed to determine the associations between workload, perceived organizational support, work engagement, and psychological wellbeing. Results The findings unveiled compelling negative associations between workload and perceived organizational support, workload and work engagement, and workload and psychological wellbeing among the secondary school teachers. Conversely, positive correlations emerged between perceived organizational support, work engagement, and psychological wellbeing. The structural equation modeling analysis demonstrated strong fit indices, affirming robust alignment with the anticipated models. Discussion Mediation analyses further elucidated the significance of work engagement as a mediator in the relationships between workload and psychological wellbeing, as well as between perceived organizational support and psychological wellbeing. These results underscore the pivotal role of work engagement in shaping the impact of workload and organizational support on the psychological wellbeing of secondary school teachers in Chinese educational settings.